Motivasi Peserta Aktivitas Buru Babi Sebagai Olahraga Rekreasi Di Kecamatan Tanjung Mutiara - Muhamad Ryndo; Pudia M Indika; Sonya Nelson; Anggun Permata Sari (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The problem found is that the motivation of the pig hunting participants in North Tiku District is not known. The purpose of this study was to determine the motivation of the perpetrators in carrying out pig hunting activities for recreational sports in North Tiku District. This type of research uses descriptive quantitative. The population in this study were 100 pig hunting participants. The sample of this study amounted to 100 people. The sample of this study used total sampling. The data collection method used is the distribution of questionnaires. The instrument used is a questionnaire. The data analysis technique used is histogram graph with percentage calculation. Based on the results of data calculations, it is known that from 100 respondents who carry out pig hunting activities, it is known that the highest indicator is the talent indicator with a percentage of 85.80% with an average answer score of 4.29. Motivation with the lowest indicator is pleasure with a percentage of 72% with an average score of 3.61